أهمية جودة الخصائص النوعية للمعلومات المحاسبية والمالية في ترشيد قرارات الأطراف الداخلية والخارجية للمؤسسة الاقتصادية - دراسة تحليلية- - قمان, عمر (Université de M'sila, 2019)
تهدف هذه الدراسة إلى التعريف بالخصائص النوعية للمعلومات المحاسبية والمالية وإبراز أهميتها لما لها من أثر مباشر على القرارات التي يتم اتخاذها على أساسها، حيث توجد العديد من العوامل والاعتبارات التي تحكمها وتحددها ينبغي أخذها بعين الاعتبار مثل الموثوقية والملائمة..، فهذه العوامل الخاصة بالمعلومات المحاسبية والمالية جد مهمة بالنسبة لمستخدميها. وانطلاقا من الأهمية البالغة للمعلومات المحاسبية والمالية في الحياة الاقتصادية، أصبح من الضروري الاهتمام بالخصائص النوعية للمعلومات المحاسبية والمالية وجودتها والبحث عن سبل قياس جودتها بغية ترشيد القرارات، وأيضا البحث عن كل العوامل المؤثرة عليها. Summary: The objective of this study is to identify the specific characteristics of accounting and financial information and discovery best part of importance because of its direct impact on the decisions taken on its basis. There are many factors and considerations that govern and determine which should be taken into consideration such as reliability and suitability. exceptionally important for its users. known the importance of accounting and financial information in economic life, it became necessary to pay attention to the specific characteristics and quality of accounting and financial information and to seek ways of measuring their quality in order to rationalize decisions, as well as to search for all factors affecting them. Keywords: reliability, relevance, quality of accounting and financial information.
Keywords: الموثوقية، الملاءمة، جودة المعلومات المحاسبية والمالية.